Content Validity Analysis of Arabic Language Textbooks for Eleventh ‎Graders of Madrasah Aliyah According to the National Education ‎Standards Authority - Khuntum Khaira Ummah; Rahmat Satria Dinata (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
In the book of teaching the Arabic language for the eleventh grade in ‎the Islamic High School in 2020, the researcher found some differences ‎and errors in the presentation of educational materials. This research ‎aims to reveal the validity of the content validity of the textbook for ‎teaching the Arabic language for the eleventh grade in the Islamic High ‎School in 2020 according to the National Education Reporting ‎Authority (BSNP). This research is important for his work, because this ‎book that the teacher will use as the main teaching material in ‎teaching Arabic to eleventh grade students in the Islamic High School ‎throughout Indonesia, then this book must be a decent book as the ‎main teaching material. The research approach used in this research is ‎a qualitative approach with a library approach. As for the data ‎collection tools, it is the notes in the book for teaching the Arabic ‎language for the eleventh grade in the high school in 2020 and the ‎documents for collecting written data related to this research. The ‎data analysis method in this research is content analysis. As for the ‎data analysis steps in this research, they are data identification, analysis ‎process, and degree assignment. The results of this research were that ‎the suitability of the materials with the main competency and the basic ‎competence in this book is decent, but the spiritual attitude and the ‎social attitude need to be fulfilled in each lesson. The accuracy of the ‎material in this book was a little decent, because the error was found in ‎the movement of the word and the statement of the material. The ‎terminology and diction were found to be inappropriate with the well-‎known Arabic terminology, and some of the pictures and illustrations ‎were not appropriate for their statement. The replenishment of ‎material in this book was decent, but some of the photos and ‎illustrations are unrealistic. There are the examples and the issue that ‎do not indicate the examples and the issue found in Indonesia and the ‎Arabs‎